Theoretical analysis of thermal destruction of dimethyl phosphates immobilized on dispersed silica surface - Kukueva, V.V.; Kirilov, O.A.; Grebenyuk, A.G.; Lobanov, V.V. (Поверхность, 2002)
The calculations on the electronic and space structure have been carried out for both trimethyl phosphate molecule and that supported at silica surface within the frameworks of the SCF MO LCAO MNDO valence approximation. The routes of these systems destruction have been studied. The decomposition of trimethyl phosphate molecule chemically immobilized onto fumed silica surface has been shown to occur with absorption of small heat quantity (~19.1 kcal/mol). This explains a high effectiveness of the use of silicas modified by organic phosphorus derivatives as active components of fire-extinguishing powders.